Isolation, Identification and Antibacterial Activity of Lactic Acid Bacteria Isolated From Traditionally Fermented Raw Milk (Journal of Environmental Bioremediation and Toxicology, 2024)
Lactic acid bacteria are well known for their antibacterial activity against pathogenic and spoilage organisms. This study was conducted to determine the antibacterial activity of lactic acid bacteria isolated from traditionally fermented raw milk on E.coli and S. aureus. Three (3) Lactic acid bacteria species were isolated from traditionally fermented raw milk samples collected from different areas within Gombe metropolis. The isolates were identified using cultural, microscopic and biochemical test. The antibacterial activity of the lactic acid bacteria species against E. coli and S. aureus was determined using overlay method. All the different isolates showed growth inhibitory activity against E. coli and S. aureus with sample from Herwagana having the highest average growth inhibitory activity of 17.5 mm on E. coli. The Lactic acid bacteria isolates from traditionally fermented raw milk were shown to have activity on bacterial pathogens. The bacteriocin produced by LAB might be used as the valid candidates of preservative against foodborne pathogens.
Keywords: Lactic acid bacteria; Antibacterial activity; Traditionally fermented milk; Escherichia coli; Staphylococcus aureus